Effectiveness of midwife/nurse-led non-invasive uterine massage in preventing postpartum haemorrhage: a quantitative systematic review protocol - Puangpaka Kongvattananon; Boonsurb Sosome; Sopen Chunuan; Treechada Punsomreung; Panida Varachanonth; Patraporn Bhatarasakoon (BMJ Open)
Introduction Postpartum haemorrhage (PPH) negatively impacts women’s health. Preventing and managing PPH is important, and nurse-led interventions are needed. However, no systematic review has evaluated the effectiveness of non-invasive uterine massage for PPH prevention. Therefore, this systematic review aims to assess the efficacy of midwife/nurse-led intervention in managing PPH, serving as the best available evidence to develop further guidelines and recommendations in practice and policy-making.Methods and analysis This systematic review will follow the JBI methodology for systematic reviews of effectiveness. The search will be conducted in the MEDLINE (PubMed), CINAHL (EBSCO), BENTHUM Science, JBI, Cochrane, ThaiJo and Google Scholar databases. Studies will be included in English and Thai and published between 2015 and 2024. Two independent reviewers will conduct the review, with data extraction and quality evaluation. Studies will be pooled in a statistical meta-analysis using JBI System for the Unified Management, Assessment and Review of Information or other software where possible.Ethics and dissemination This systematic review does not require formal ethical approval because all data will be analysed anonymously. The results will provide an overall review and evidence of midwife/nurse-led non-invasive uterine massage intervention in preventing PPH. These findings will be disseminated through peer-reviewed publications.PROSPERO registration number CRD42024566382